The impact of information on improving administrative leadership: A case study of Condor Corporation - Zouarqui, Imane; Abdelkader, Mouzaoui (The International tax journal, 2026)
The industrial sector plays an important and pivotal role thanks to its contribution to the economic life. In this context, the rapid developments in the industrial and economic environments oblige companies to adapt with them to make profits, increase competitiveness, and survive. This cannot be achieved unless with a good administration that provides quality information to help the leaders take the suitable decisions towards the target goals. Thus, this paper aims at knowing the effect of the information quality with its main dimensions that include the accuracy and clarity, timeliness, flexibility, and inclusion on the promotion of the administrative leadership in Condor Electronics Company in Bordj Bou Arriridj, Algeria. Findings show a statistically significant relation between the information quality with its dimensions and the promotion of the administrative leadership. Besides, the study suggests holding training sessions for the directors and decision makers to raise their awareness about the administrative leadership.